Jazz Interpretations of Classical Musical Works - Stacy Olive Jarvıs (Konservatoryum)
This study aims to elucidate the interpretation of jazz music within the classical mu sic domain through specific works, examining the improvisations and arrangements of jazz music on compositions from various periods of classical music. It assesses themes of improvisation in both classical and jazz music, as well as the interpretations of jazz music within aclassical context. The selected musical material provides an op portunity for analytical examination of various forms of classical music representation in piano jazz and identifying the mechanisms of ‘translating’ academic compositions into thelanguageofjazzart.Theresearchdemonstratesthatthetransformationofclas sical sources occurs at intonational, harmonic-modal, metrorhythmic, and structural levels. By characterising piano jazz and tracing its multifaceted history, the author highlights the main directions characteristic of performance on this instrument.